Older male mentors' perceptions of a Men's Shed intergenerational mentoring program - Wilson, N.; Cordier, Reinie; Whatley, L. (Wiley-Blackwell Publishing Asia, 2013)
Background/aim: The National Male Health Policy identifies several groups of males at different transitional life stages that are at particular risk, including teenage boys at risk of social exclusion and recently retired older men. A novel intergenerational mentoring program was developed to bring these groups together through participation in meaningful occupation. This research aimed to investigate the mentors' experiences of the program, their views about the teenage boys and the structure of the program.Methods: Nine teenage boys (14–16 years) at risk of social exclusion participated in a weekly shared construction project with older male mentors (60–75 years) at a local Sydney school over one school term. A post-project focus group and individual interviews were conducted with six of the mentors pre- and post-project. Data were analysed using the constant comparative method of grounded theory; all authors developed themes individually and then collectively.Results: The core theme that emerged was a values-led male reconnection. Centred in themes of gendered valuing, respect, tradition and the handing down of life experience, occupational engagement was integral to bridging the generational gap and facilitating intergeneration discourse.Conclusion: Older males with a strong sense of generativity are a valuable resource in delivering such programs, and reported a sense of accomplishment and enhanced self-worth. Given the central role that occupational engagement played in fusing the project, this study highlights the untapped role of occupational therapy in developing programs aimed at promoting the health and wellbeing of Australian men.